2003
DOI: 10.1203/01.pdr.0000072796.25097.a5
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Mitochondrial DNA Depletion

Abstract: Mitochondria are believed to be direct descendants of a bacterial endosymbiont (most likely Rickettsia prowazekii) that became established~1.5 billion years ago, in a nucleuscontaining host cell. The low gene content of mammalian mtDNA compared with even the smallest known eubacterial genomes appears to imply a relatively rapid and extensive loss or transfer of genetic information from the mitochondria to the nucleus and a compensatory import of nuclear encoded proteins into the mitochondria (1). It is not com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 61 publications
(49 reference statements)
0
9
0
1
Order By: Relevance
“…Genetic 'mtDNA depletion syndromes' 48,49 offer support for the reasoning used in generating these experimental models and for the data obtained from them. In those illnesses, mitochondrial and cytoplasmic nucleotide pools are disturbed by mutations of kinases, transporters, and enzymes involved in nucleotide pool homeostasis.…”
Section: Tg Y955cmentioning
confidence: 92%
“…Genetic 'mtDNA depletion syndromes' 48,49 offer support for the reasoning used in generating these experimental models and for the data obtained from them. In those illnesses, mitochondrial and cytoplasmic nucleotide pools are disturbed by mutations of kinases, transporters, and enzymes involved in nucleotide pool homeostasis.…”
Section: Tg Y955cmentioning
confidence: 92%
“…Mitochondrial DNA depletion syndromes are caused by defects of mtDNA replication and maintenance of deoxynucleotide pools and are transmitted mainly in an autosomal recessive fashion. 55 In the published literature, deafness has been reported in a phenotype characterized by a late onset and slower progression in four children with multi-systemic involvement and mtDNA depletion. Three of these patients met diagnostic criteria for Kearns-Sayre syndrome which has not been typically associated with mitochondrial DNA depletion.…”
Section: Mitochondrial Ribosomal Rna Gene Mutationsmentioning
confidence: 99%
“…56 The median age of onset of hearing loss in our patients with mtDNA depletion was thirteen years. Since the majority of the patients affected with mtDNA depletion syndromes usually have an earlier onset and more severe course, 55 it is possible that many of the patients described in the literature have succumbed prior to any formal hearing evaluation.…”
Section: Mitochondrial Ribosomal Rna Gene Mutationsmentioning
confidence: 99%
“…This observation may open new possibilities for further therapy trials and may explain the occasionally observed reversibility of mtDNA depletion [47–49]. The mechanisms, however, underlying the expression of tissue selectivity and the reversibility remain still unclear [50, 51].…”
Section: Discussionmentioning
confidence: 99%